Assessing the Viability of Extended Nonmetal Atom Chains in MnF4n+2 (M=S and Se)1. Issue 5 (4th December 2014) - Popov, Ivan A.; Averkiev, Boris B.; Starikova, Alyona A.; Boldyrev, Alexander I.; Minyaev, Ruslan M.; Minkin, Vladimir I.
Abstract Theoretical investigations to evaluate the viability of extended nonmetal atom chains on the basis of molecular models with the general formula MnF4n+2 (M=S and Se) and corresponding solid‐state systems exhibiting direct SS or SeSe bonding were performed. The proposed high‐symmetry molecules were found to be minima on the potential energy surface for all SnF4n+2 systems studied (n=2–9) and for selenium analogues up to n=6. Phonon calculations of periodic structures confirmed the dynamic stability of the ‐(SF4–SF4)∞‐ chain, whereas the analogous ‐(SeF4–SeF4)∞‐ chain was found to have a number of imaginary phonon frequencies. Chemical bonding analysis of the dynamically stable ‐(SF4–SF4)∞‐ structure revealed a multicenter character of the SS and SF bonds. A novel definition and abbreviation (ENAC) are proposed by analogy with extended metal atom chain (EMAC) complexes.